2007
DOI: 10.1183/09031936.00150006
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide relates to cough sensitivity in children with chronic cough

Abstract: Airway neuropeptides, in particular calcitonin gene-related peptide (CGRP), are likely to be important in the pathogenesis of chronic cough. The present authors evaluated the following: 1) the relationship between cough sensitivity and bronchoalveolar lavage (BAL) neuropeptides; and 2) the effect of reflux oesophagitis (RO) on cough, cough sensitivity and BAL neuropeptides in children not selected for cough. It was hypothesised that CGRP would be increased in children with chronic cough and would relate to cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 44 publications
(73 reference statements)
4
19
0
Order By: Relevance
“…The sensitizing effect of SP on RARs has also been demonstrated in the central nervous system, especially in the nucleus tractus solitarius, which also results in an enhanced cough reflex [38,39]. While airway SP levels or expression in patients with persistent cough are conflicting [10,11,12,13,40,41], we found elevated plasma SP levels in patients with persistent asthmatic and nonasthmatic cough.…”
Section: Discussionmentioning
confidence: 37%
“…The sensitizing effect of SP on RARs has also been demonstrated in the central nervous system, especially in the nucleus tractus solitarius, which also results in an enhanced cough reflex [38,39]. While airway SP levels or expression in patients with persistent cough are conflicting [10,11,12,13,40,41], we found elevated plasma SP levels in patients with persistent asthmatic and nonasthmatic cough.…”
Section: Discussionmentioning
confidence: 37%
“…In the same study when lignocaine was instilled topically onto the oesophagus, cough was prevented. We have previously demonstrated that distal oesophageal acid exposure may be associated with increased airway neuropeptide levels, supporting the relationship between acid reflux and airway nerve activation 18 19. Lang et al 20 have shown that in anaesthetised cats, applying acid to the oesophagus was associated with a bronchoconstriction and increased mucus secretion in the airway.…”
Section: Mechanism Of Gord-associated Respiratory and Laryngeal Symptomssupporting
confidence: 57%
“…In an experimental model of itch, tryptase is known to activate the proteinase activated receptor (PAR-2) located on the C-fibre nerve terminal, releasing substance P which in turn sensitises the mast cell to release TNFα which in known to sensitize nociceptor function [64]. Neuropeptides such as substance P and neurokinin A are elevated in the airways of asthmatic patients with cough [65] and airway levels of calcitoningene-related peptide (CGRP) are positively correlated with capsaicin cough reflex sensitivity [66].…”
Section: Inflammation Cough Reflex Sensitisation and Airway Sensory mentioning
confidence: 99%